Risk of postoperative major adverse cerebrovascular events in patients with spontaneous intracranial hematoma stratified by type 2 diabetes mellitus - Yang, Junhua; Wang, Sihui; Ji, Xiangtian; Sun, Yu; Feng, Jingyu; Liu, Bin; Yang, Jun (Frontiers in Human Neuroscience, 2025)
Background and purposeDiabetes Mellitus (DM) is a common concomitant disease of spontaneous intracranial hemorrhage (ICH). Postoperative major adverse cerebrovascular events (post-MACEs) may diminish the surgical benefits of patients with ICH. However, evidence regarding the impact of DM on post-MACEs remains limited.MethodsThis was a multicenter cohort study that enrolled ICH patients presenting to eight neurosurgery departments between January 1, 2015, and May 31, 2021. Patients were categorized into DM group and no diabetes mellitus (nDM) group, based on the presence or absence of DM. Intergroup comparisons were performed using chi-square tests for categorical variables and Mann–Whitney U tests for continuous variables. Multivariate logistic regression analysis was conducted to assess the impact of DM on post-MACEs and 30-days mortality after adjusting for confounding factors. A stratified analysis was also conducted based on the type of post-MACEs.ResultsA total of 688 ICH patients were included in the study, of whom 576 (83.7%) were classified into the nDM group and 112 (16.3%) into the DM group. Compared with the nDM group, the DM group exhibited significantly higher incidences of overall post-MACEs (28.6%), ischemic post-MACEs (14.3%), hemorrhagic post-MACEs (23.2%), and 30-days mortality (9.8%). After adjusting for potential confounding factors including sex, age, alcohol, coronary heart disease, dyslipidemia, antiplatelet therapy, and intraventricular hemorrhage, DM remained a significant predictor of overall post-MACEs (OR: 1.790, 95%CI: 1.072–2.990, p = 0.026), ischemic post-MACEs (OR: 2.139, 95%CI: 1.090–4.197, p = 0.027), hemorrhagic post-MACEs (OR: 1.778, 95%CI: 1.015–3.114, p = 0.044), and 30-days mortality (OR: 3.593, 95%CI: 1.536–8.406, p = 0.003).ConclusionIn conclusion, this study demonstrates that DM serves as a significant risk factor for ischemic post-MACEs, hemorrhagic post-MACEs, and 30-days mortality among patients with ICH.